Overseas employment and remittances to a dual economy. - McCormick, Barry; Wahba, Jackline (Economic Journal, 2000)
Overseas employment has become more commonplace, and remittances have increased in similar proportions. For poor countries, remittances often substantially, influence domestic expenditures and real exchange rates. We study overseas employment, remittances and domestic underemployment in a simple general equilibrium model with a non-traded good and minimum wage. The influence of population growth, rural productivity, and family altruism are examined. If remittances per migrant exceed domestic productivity then multiple equilibria may occur exhibiting high or low overseas employment. We discuss how the equilibrium with highest overseas employment conditionally Pareto dominates the other equilibria, and analyse policy co-ordination. Reproduced by permission of the publisher.